Two Decades of Lexicographica Series Maior - Hartmann, Reinhard (Lexikos, 2004)
Abstract: This article is a personal account, from the point of view of one of its editors, of thepublishing history of Lexicographica Series Maior.Keywords: LEXICOGRAPHICA SERIES MAIOR, PUBLISHING HISTORY, METALEXICOGRAPHY,LEXICOGRAPHYOpsomming: Twee dekades van Lexicographica Series Maior. Hierdie artikel is'n persoonlike weergawe, uit die gesigspunt van een van sy redakteurs, van die publikasiegeskiedenisvan Lexicographica Series Maior.Sleutelwoorde: LEXICOGRAPHICA SERIES MAIOR, PUBLIKASIEGESKIEDENIS, METALEKSIKOGRAFIE, LEKSIKOGRAFIE